Biomarkers in diagnostics of acute kidney injury after the organ-preserving surgery of localized renal cancer - S. N. Dimitriadi; E. M. Frantsiyants; N. D. Ushakova; D. A. Rozenko; A. V. Velichko (Медицинский вестник Юга России, 2018)
Objective: to assess perspectives using biomarkers for early detection of developing acute kidney injury (AKI) among patients during partial nephrectomy under the warm ischemia of the kidney. Materials and methods: data of 100 patients was assessed with a localized renal cancer Т1N0М0 aged 56,5±8,7 years. All the patients underwent partial nephrectomy under warm ischemia of the kidney. The concentration of the following “early markers of AKI” was tested in blood of the patients using the ELISA technique and standard test-systems: cystatin С (BioVendor, Czech Republic), NGAL (BCMDiagnostics, USA), L-FABP (Hycult Biotechnology, Netherlands). The duration of warm ischemia was also fixed and the rate of diuresis was valued either. The test was carried out 24 hours prior to and 16 hours after the surgical interference. All the patients were diagnosed and classified by the presence or absence of AKI during the early postoperative period according to the generally accepted classification KDIGO. The obtained results were processed with the help of Microsoft Excel software, the statistical reliability of the results was defined on the basis of the use of Wilcoxon non-parametric test. Simultaneously the expert analysis of the clinical data and results of the laboratory research was carried out. Results: the method of the early diagnostics of AKI among patients who underwent partial nephrectomy under the warm ischemia of the kidney was developed. The method is based on the successive identification of the concentration of the early biochemical markers of AKI, the duration of warm ischemia and the rate of diuresis. Conclusions: the use of the developed method allows diagnosing the development of AKI among patients undergoing partial nephretomy under the warm ischemia already in 16 hours after the surgical interference (before the rise in the creatinine level).